Sistem Pakar Untuk Mendiagnosa Penyakit Bakteri Pada Ayam Petelur Menggunakan Metode Variable Centered Intelligent Rule System (VCIRS) dan Certainty Factor Berbasis Website (Studi Kasus: Peternakan Ayam Petelur Di Tahura) - Andreswari, Desi; Suteky, Tatik; Winda P, Desi Ade (Rekursif: Jurnal Informatika, 2024)
Laying chickens are a type of poultry that is in demand by the public. One of the commodities currently being developed in Indonesia is poultry because the eggs produced are very much in demand by the Indonesian people. However, to achieve egg production and produce good eggs and make quite a large profit, farmers must pay attention to health and take good care of laying hens so that they are not susceptible to disease. There are several types of diseases that attack laying hens, one of which is a type of bacteria that causes many chickens to die and egg production decreases. Therefore, we need a system that can diagnose bacterial diseases in laying hens by applying the web-based Variable-Centered Intelligent Rule System and Certainty Factor methods, so that this system can help breeders solve problems without having to meet with experts directly. Test results from 25 test data carried out, this system is able to diagnose bacterial diseases correctly with an accuracy value of 92%. It can be concluded that this system can diagnose bacterial diseases in laying hens well. Keywords: Laying Chickens, Disease, Variable-Centered Intelligent Rule System, Certainty Factor, Expert System.